Research handbook on the law of international organizations - Klabbers, Jan (Cheltenham GB, 2011)
Focuses on the themes of functionalism and constitutionalism and how the paradign shift towards controlling international bureaucracies instead of giving them carte blanche to do as they see fit is affecting the various doctrinal issues that make up the law of international organisations. Examines the UN and EU.